Stimulus-dependent central processing of auditory stimuli: a PET study. - Mirz F; Ovesen T; Ishizu K; Johannsen P; Madsen S; Gjedde A; Pedersen CB (Scandinavian Audiology)
Positron emission tomography (PET) was used to investigate the neural systems involved in the central processing of different auditory stimuli. Noise, pure tone and pure-tone pulses, music and speech were presented monaurally. 0-15-water PET scans were obtained in relation to these stimulations presented to five normal hearing and healthy subjects. All stimuli were related to a basic scan in silence. Processing of simple auditory stimuli, such as pure tones and noise, predominantly activate the left transverse temporal gyrus (Brodmann area [BA] 41), whereas sounds with discontinued acoustic patterns, such as pure-tone pulse trains, activated parts of the auditory association area in the superior temporal gyri (BA 42) in both hemispheres. Moreover, sounds with complex spectral, intensity, and temporal structures (words, speech, music) activated spatially even more extensive associative auditory areas in both hemispheres (BA 21, 22). PET has revealed a remarkable potential to investigate early central auditory processing, and has provided evidence of the coexistence of functionally linked, but individually active parallel and serial auditory networks.